Exploring athletes` perceptions of coach stress in elite sport environments - Thelwell, R. C.; Wagstaff, C. R. D.; Rayner, A.; Chapman, M.; Barker, J. (Journal of Sports Sciences, 2017)
Abstract: The present study aimed to extend research that has focused on the identification of stressors associated with coaching practice by systematically evaluating how such stressors effect athletes, and more broadly, the coach-athlete relationship. A total of 13 professional- and national-level athletes were interviewed to address the three study aims: how they detect when a coach is encountering stressors, how coach experiences of stress effects them as an athlete, and how effective the coach is when experiencing stress. Following content analysis, the data suggested athletes were able to detect when a coach was experiencing stress and this was typically via a variety of verbal and behavioural cues. Despite some positive effects of the coach experiencing stress, the majority were negative and varied across a range of personal influences on the athlete, and effects on the general coaching environment. It was also the broad view of the athletes that coaches were less effective when stressed, and this was reflected in performance expectations, perceptions of competence, and lack of awareness. The findings are discussed in relation to the existing theory and with reference to their implications for applied practice, future research, and development of the coach-athlete relationship.